Zonation pattern on rocky shore of Lima Department - Paredes, Carlos (1974)
Biocenological zonation along the rocky shore of Department of Lima, Peru, were studied in 1972 and part of 1973 in order to establish a scheme of applicable zonation among others most used around the world. High and low water levels of spring tides and neap tides were delimited in seven areas selected as guide, in these areas have been determinate the vertical distribution of organisms, associations and communities characteristics in such subdivision of the intertidal zone. Stephenson and Stephenson's model of zonation was found applicable with certain modifications: The LITTORAL ZONE extends from upper level of Littorina peruviana to the mean level of ordinary low spring tides (MLWS = O m), and includes: (a) Supralittoral fringe, extends from the upper level of Littorina peruviana to the high level of Chthamalus cirratus.(b) Midlittorol zone, extends from the lower limit of supralittoral fringe to the upper level of Megabalanus psittacus; and (c) Infralittoral fringe, extends from the lower limit of the midlittoral zone to the mean line of ordinary low spring tides.